1997
DOI: 10.1128/jcm.35.3.799-801.1997
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of IS6110-based amplification assays for Mycobacterium tuberculosis complex

Abstract: We have demonstrated homology between DNA from mycobacteria other than tuberculosis strains (MOTT) and a central region of IS6110 and have urged caution in using diagnostic tests based on this target (6). Hellyer and colleagues (5) have evaluated three IS6110-based amplification methods: HincII strand displacement amplification (SDA), thermophilic SDA, and a previously described PCR (11) and have observed no cross-reaction with 27 nontuberculosis mycobacteria, 26 of which had been used previously in our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…This may perhaps account for the rates of false-positive results that were observed in several studies that used IS6110 as a target sequence and that ranged from 2.3% (18) to 20% (34). More recently, IS6110 was shown to hybridize to PCR products amplified from Streptococcus pneumoniae, Streptococcus pyogenes, and even from Aspergillus fumigatus (19,20). In addition to being prone to false-positive results, targeting of IS6110 for PCR amplification may also yield false-negative results.…”
Section: Resultsmentioning
confidence: 99%
“…This may perhaps account for the rates of false-positive results that were observed in several studies that used IS6110 as a target sequence and that ranged from 2.3% (18) to 20% (34). More recently, IS6110 was shown to hybridize to PCR products amplified from Streptococcus pneumoniae, Streptococcus pyogenes, and even from Aspergillus fumigatus (19,20). In addition to being prone to false-positive results, targeting of IS6110 for PCR amplification may also yield false-negative results.…”
Section: Resultsmentioning
confidence: 99%
“…False positives were also demonstrated by a nested IS6110 based PCR for the detection of Mycobacterium tuberculosis when applied to mycobacteria that did not belong to the M. tuberculosis complex [9]. More recently, ampli¢ed DNA from Aspergillus spp., Streptococcus pneumoniae and S. pyogenes was found to hybridise to a probe derived from a 181-bp fragment of M. tuberculosis IS6110 [10]. Trinker et al [11] have also reported false-positive diagnosis of tuberculosis with the insertion sequence IS6110 leading to the commencement of inappropriate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…False positives were also demonstrated by a nested IS 6110 based PCR for the detection of Mycobacterium tuberculosis when applied to mycobacteria that did not belong to the M. tuberculosis complex [9]. More recently, amplified DNA from Aspergillus spp., Streptococcus pneumoniae and S. pyogenes was found to hybridise to a probe derived from a 181‐bp fragment of M. tuberculosis IS 6110 [10]. Trinker et al [11] have also reported false‐positive diagnosis of tuberculosis with the insertion sequence IS 6110 leading to the commencement of inappropriate treatment.…”
Section: Discussionmentioning
confidence: 99%